2021
DOI: 10.1017/cjn.2021.312
|View full text |Cite
|
Sign up to set email alerts
|

P.030 Long-term Safety and Tolerability of Atogepant 60 mg Following Once-Daily Dosing Over 1 Year for the Preventive Treatment of Migraine

Abstract: Background: The goal of the study was to assess the safety and tolerability of atogepant, an oral, calcitonin gene-related peptide receptor antagonist in development for migraine preventive treatment, once daily over 1 year. Methods: Multicenter, open-label trial (NCT03700320). Adults with migraine were randomized 5:2 to atogepant or oral standard-of-care (SOC) migraine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…The 12-week treatment duration is not adequate to assess the long-term efficacy and side effects of atogepant. In this regard, atogepant 60 mg administered once daily to patients with episodic migraine over a 52-week open-label, multicenter, phase III extension study (NCT03700320) was efficacious to reduce monthly migraine days, was associated with improvements in function and health-related quality of life, and rates of response increased throughout the course of the trial; further, the treatment was generally well tolerated with no new safety concerns identified [54][55][56]. A number of other studies are ongoing to evaluate the long-term safety and tolerability of atogepant in adult patients with episodic (NCT03939312) and episodic or chronic (NCT04686136 and NCT04437433) migraine.…”
Section: Discussionmentioning
confidence: 99%
“…The 12-week treatment duration is not adequate to assess the long-term efficacy and side effects of atogepant. In this regard, atogepant 60 mg administered once daily to patients with episodic migraine over a 52-week open-label, multicenter, phase III extension study (NCT03700320) was efficacious to reduce monthly migraine days, was associated with improvements in function and health-related quality of life, and rates of response increased throughout the course of the trial; further, the treatment was generally well tolerated with no new safety concerns identified [54][55][56]. A number of other studies are ongoing to evaluate the long-term safety and tolerability of atogepant in adult patients with episodic (NCT03939312) and episodic or chronic (NCT04686136 and NCT04437433) migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use of atogepant 60 mg for one year was tolerated, with 18% of adverse events considered to be related to the drug, namely upper respiratory tract infection, constipation, nausea, and urinary tract infection. None of the serious adverse events were considered related to the drug [ 61 ]. When administered in a single oral dose of 60 mg, atogepant was well tolerated in patients with hepatic impairment, with similar plasma levels, but increased systemic exposures to atogepant did not have a clinical translation [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“… 32 The investigators reported no serious adverse events related to atogepant. 32 Cases of ALT or AST greater than three times ULN were reported in 2.4% (13/531) of participants in the atogepant group and 3.2% (6/109) in the standard of care group. 32 No cases of Hy’s Law were reported.…”
Section: Introductionmentioning
confidence: 93%
“… 32 Discontinuation due to adverse events occurred in 5.7% in the atogepant group. 32 The investigators reported no serious adverse events related to atogepant. 32 Cases of ALT or AST greater than three times ULN were reported in 2.4% (13/531) of participants in the atogepant group and 3.2% (6/109) in the standard of care group.…”
Section: Introductionmentioning
confidence: 98%